Biodegradable iron-silicon implants produced by additive manufacturing. (1st May 2022) - Bondareva, J V; Dubinin, O N; Kuzminova, Y O; Shpichka, A I; Kosheleva, N V; Lychagin, A V; Shibalova, A A; Pozdnyakov, A A; Akhatov, I S; Timashev, P S; Evlashin, S A
Abstract: Due to many negative and undesirable side effects from the use of permanent implants, the development of temporary implants based on biocompatible and biodegradable materials is a promising area of modern medicine. In the presented study, we have investigated complex-shaped iron-silicon (Fe–Si) scaffolds that can be used as potential biodegradable framework structures for solid implants for bone grafting. Since iron and silicon are biocompatible materials, and their alloy should also have biocompatibility. It has been demonstrated that cells, mesenchymal stromal cells derived from the human umbilical cord (UC-MSC) and 3T3, were attached to, spread, and proliferated on the Fe–Si scaffolds' surface. Most of UC-MSC and 3T3 remained viable, only single dead cells were observed. According to the results of biological testing, the scaffolds have shown that deposition of calcium phosphate particles occurs on day one in the scaffold at the defect site that can be used as a primary marker of osteodifferentiation. These results demonstrate that the 3D-printed porous iron-silicon (Fe–Si) alloy scaffolds are promising structures for bone grafting and regeneration.